Which is more effective for pain relief during fractionated carbon dioxide laser treatment: EMLA cream or forced cold air anesthesia?. (2nd January 2018) - Sari, Elif; Bakar, Bulent
ABSTRACT: Background and aim : The aim of this study was to compare the effectiveness of a eutectic mixture of local anesthetic (EMLA) cream and forced cold air anesthesia (FCAA) on pain control during ablative fractionated carbon dioxide (CO2 ) laser treatment.Methods : Fifteen volunteers participated in this prospective, controlled, split-face clinical study. EMLA cream was applied 60 minutes before the laser procedure on half of the face, and FCAA was performed on each subunit of the other half of the face. The laser procedure was performed on each half of the face. Patients rated their pain during the procedure using a pain scale scored from 0–10. Both doctor and nurse rated patient discomfort during the procedure using a scale scored from 0–10. The pain scores associated with both EMLA and FCAA sides of the face were compared statistically.Results : Patient pain scores and discomfort scores detected by doctor and nurse were not statistically different between EMLA and FCAA. There was no statistically significant difference between males and females.Conclusion : Instead of using EMLA, FCAA—which can be applied in a shorter time—may be a cost-effective, simple, and safe local anesthesia method used in the ablative fractionated CO2 laser procedure.